Implementação dos Editais Tipo na contratação estatal de obras de infraestrutura rodoviária: um estudo dos seus benefícios - Alca Cruz , María Yesica; Alvarez-Rozas, Karin (Gestionar: revista de empresa y gobierno, 2024)
State-managed electricity generation companies in Peru have experienced a decline in their financial profitability from 10.26% to 6.73% between the years 2015 and 2018, preceded by growth from 4.20% to 10.26% between 2008 and 2015. The financial profitability of these companies showed a decrease of 34.38% in 2018 compared to 2015. The research aimed to identify the determinants of the financial profitability of state-managed electricity generation companies in Peru during the period 2008-2018, thus evaluating the financial behavior and the influence of economic and financial determinants on the profitability of these companies, using an econometric panel data model proposed by Arellano and Bond through the generalized method of moments. The results found that financial profitability defines the business benefit of electricity generation companies, with sales revenue behavior, economic growth, cost of sales, financial leverage index, and inflation being determinants for the variation in financial profitability. It is concluded that sales revenue and Gross Domestic Product (GDP) directly influence financial profitability, while the consumer price index (inflation), financial leverage, and cost of sales indirectly influence the financial profitability of electricity generation companies.